Time-resolved fluorescence study of a calcium-induced conformational change in prothrombin fragment 1 - Hof, M; Fleming, G R; Fidler, V (Proteins, 1996)
The wavelength dependent fluorescence decay properties of bovine prothrombin fragment 1 have been investigated employing a picosecond time-correlated single photon counting technique. All observations are discussed with using the crystal structure (Soriano-Garcia et al., Biochemistry 31:2554-2566, 1992). Fluorescence lifetimes distribution and conventional multiexponential analysis, as well as acrylamide quenching studies lead to the identification of six distinguishable tryptophan excited-states. Accessibility to the quencher and the known structure are used to associate a fluorescence decay of the tryptophan present in the Gla domain (Trp42) with two red shifted components (2.3 and 4.9 ns). The two kringle domain tryptophans (Trp90 and Trp126) exhibit four decay times (0.06, 0.24, 0.68, and 2.3 ns), which are blue shifted. The calcium-induced fluorescence quenching is a result of static quenching: the five decay times remain unchanged, whereas the fluorescence intensity of Trp42 is decreased. The static quenching process is a consequence of a ground state interaction between the Cys18-Cys23 disulfide bridge and Trp42. The monomolecular equilibrium constant for this disulfide-pi-electron interaction is found as 4.8.
Keywords: Calcium; Acrylamide; Prothrombin; skot; tryptofan; zvířata; protrombin; akrylamidy; Cattle; Peptide Fragments; proteinové prekurzory; vápník; Tryptophan; peptidové fragmenty; Spectrometry, Fluorescence; Animals; Acrylamides; akrylamid; Protein Precursors; fluorescenční spektrometrie